The Influence of Transformational Leadership on Organizational Resilience: The Mediating Role of Knowledge Management Capability - Zaidan Nawawi; Telly Pauline Ulviana Siwi; Dasmadi Dasmadi (International Journal of Digital Marketing Science, 2026)
This study examines the effect of transformational leadership on organizational resilience by investigating the mediating role of knowledge management capability. Specifically, it explores how transformational leadership strengthens organizational resilience by enhancing the organization's ability to acquire, share, and utilize knowledge effectively. A quantitative survey design was employed, with data collected from employees through purposive sampling. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to evaluate the measurement model and test the structural relationships among the variables. The results reveal that transformational leadership positively and significantly influences both knowledge management capability and organizational resilience. Knowledge management capability also has a significant positive effect on organizational resilience and partially mediates the relationship between transformational leadership and organizational resilience. These findings indicate that organizations led by transformational leaders achieve higher resilience when supported by strong knowledge management practices. The novelty of this research lies in integrating knowledge management capability as a mediating mechanism that explains how transformational leadership contributes to organizational resilience. This model provides a deeper understanding of organizational adaptation in dynamic business environments. The study contributes to the literature on leadership, knowledge management, and organizational resilience while offering practical guidance for organizational leaders to strengthen resilience through effective leadership and strategic knowledge management initiatives.